Analyses of combined Merkel cell carcinomas with neuroblastic components suggests that loss of T antigen expression in Merkel cell carcinoma may result in cell cycle arrest and neuroblastic transdifferentiation - Kervarrec, Thibault; Appenzeller, Silke; Gramlich, Susanne; Coyaud, Etienne; Bachiri, Kamel; Appay, Romain; Macagno, Nicolas; Tallet, Anne; Bonenfant, Christine; Lecorre, Yannick; Kapfer, Jean; Kettani, Sami; et al. (The journal of pathology, 2024)
Merkel cell carcinoma (MCC) is an aggressive skin cancer frequently caused by genomic integration of the Merkel cell polyomavirus (MCPyV). MCPyV-negative cases often present as combined MCCs, which represent a distinctive subset of tumors characterized by association of an MCC with a second tumor component, mostly squamous cell carcinoma. Up to now, only exceptional cases of combined MCC with neuroblastic differentiation have been reported. Herein we describe two additional combined MCCs with neuroblastic differentiation and provide comprehensive morphologic, immunohistochemical, transcriptomic, genetic and epigenetic characterization of these tumors, which both arose in elderly men and appeared as an isolated inguinal adenopathy. Microscopic examination revealed biphasic tumors combining a poorly differentiated high-grade carcinoma with a poorly differentiated neuroblastic component lacking signs of proliferation. Immunohistochemical investigation revealed keratin 20 and MCPyV T antigen (TA) in the MCC parts, while neuroblastic differentiation was confirmed in the other component in both cases. A clonal relation of the two components can be deduced from 20 and 14 shared acquired point mutations detected by whole exome analysis in both combined tumors, respectively. Spatial transcriptomics demonstrated a lower expression of stem cell marker genes such as SOX2 and MCM2 in the neuroblastic component. Interestingly, although the neuroblastic part lacked TA expression, the same genomic MCPyV integration and the same large T-truncating mutations were observed in both tumor parts. Given that neuronal transdifferentiation upon TA repression has been reported for MCC cell lines, the most likely scenario for the two combined MCC/neuroblastic tumors is that neuroblastic transdifferentiation resulted from loss of TA expression in a subset of MCC cells. Indeed, DNA methylation profiling suggests an MCC-typical cellular origin for the combined MCC/neuroblastomas. © 2024 The Author(s). The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.
Gesehen am 31.03.2025